The future of retail banking : delivering value to global customers - DiVanna, Joseph A. (New York : Palgrave Macmillan, 2004)
"This book argues that traditional retail banks are at risk of becoming non-competitive in a global marketplace unless they re-establish a value proposition designed from a customer perspective. The author develops a view in which retail banking future is an evolutionary process which must balance the need to achieve economies of scale and scope while incorporating local customer values. This book looks at financial institutions from all parts of the globe in order to address the current trends influencing competition, including globalization, market structure, technology and demographics, and how these will affect companies and their organization, business opportunities, revenue streams, branding and customer behaviour. It also shows banks how to develop strategic initiatives for future competition."--BOOK JACKET.
Ch. 1. The Nature of Banking and its Future -- Ch. 2. Getting There: Thinking Ahead -- Ch. 3. Being There: Preparing for the Future -- Ch. 4. Competing There: Competing With New Rules -- Ch. 5. Conclusion: Synergistic Banking.
Includes bibliographical references (p. 174-176) and index.
Keywords: Banks and banking; Financial services industry; Customer services -- Management; Value